RECLAIMING THE SHORELINE WITH MODULAR BIOCARBON: SEAWEED AND FLY ASH BEYOND CARBON COLONIALISM - Maysahra Ramadhani (Jurnal Geosaintek, 2026)
“Why do the exploited drown in climate debt, while the polluters sail free, taxless, shameless, and unaccountable?” Coastal ecosystems are among the Earth’s most vital yet vulnerable frontlines, threatened by erosion, seawater intrusion, sea level rise, and the compounding effects of climate change. These risks not only endanger marine biodiversity but also fracture the socio-economic lifelines of communities who did the least to cause the crisis. This innovation introduces Modular Biocarbon Technology, a nature-based, community-driven solution constructed from seaweed, a fast-growing carbon-absorbing biomass, and fly ash, an industrial byproduct rich in pozzolanic compounds. These two materials are fused into adaptive, site-specific modules that reduce wave energy, capture sediment, support marine biodiversity recovery, and most critically, serve as permanent carbon sinks through biochar stabilization. In the era of global climate injustice, where nations like Indonesia are expected to act as planetary lungs without equitable compensation. This solution reframes our ecological burden as a modular climate asset. It offers leverage in the global carbon debt discourse, asserting that frontline communities deserve agency, not austerity. Aligned with SDGs 11, 13, and 14, this solution is scalable, replicable, and deeply rooted in local participation. It empowers coastal actors to reclaim degraded shorelines, while catalyzing a circular economy that transforms industrial waste into tools of resistance and regeneration. By bridging environmental science, material innovation, and social equity, this initiative provides a bold, implementable blueprint for coastal resilience, carbon justice, and national decarbonization.